Pengembangan Perangkat Pembelajaran Matematika Berbasis Open Ended Untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa Kelas VIII Pada Materi SPLDV - Ummah, Bintana Inashlahatul; Utami, Yudy Tri; Arifandi, Moh. Zainal (UAS PRESS, 2024)
This research is motivated by the low creative thinking skills of students and there are still many teachers who have difficulty in developing learning tools that are in accordance with the demands of the 2013 curriculum learning. The purpose of this research is to develop open ended based mathematics learning tools to improve the creative thinking skills of grade VIII students on SPLDV material that is practical, valid and effective. The device development model chosen in this research is the Thiagarajan, Semmel & Semmel (4-D) model. This model consists of four stages, namely defining, designing, developing and disseminating. The learning tools developed in this research are in the form of lesson plans, student activity sheets and creative thinking skills tests. The research instruments used are in the form of device validation sheets, learning implementation observation sheets, student activity observation sheets and student response questionnaires. From the results of the validation test data analysis, the average percentage score for: (1) lesson plas which is 4.60 with a valid category, (2) Student Activity Sheet which is 4.57 with a valid category, (3) Creative Thinking Ability Test which is 4.74 with a valid category. The observation results of the implementation of learning devices showed an average result of 83.63% in the good category. The overall average of student activity is 83% which is classified as an active category. The results of the creative thinking ability test showed that the percentage of classical completeness was 80%. And students' response to the developed learning tools is positive. Thus, the open ended based learning tools developed are valid, practical and effective to improve the creative thinking ability of students in grade VIII.